2018
DOI: 10.1021/jacs.8b02902
|View full text |Cite
|
Sign up to set email alerts
|

Linearly Two-Coordinated Silicon: Transition Metal Complexes with the Functional Groups M≡Si—M and M═Si═M

Abstract: A detailed experimental and theoretical analysis is presented of unprecedented molybdenum complexes featuring a linearly coordinated, multiply bonded silicon atom. Reaction of SiBr(SIdipp) (SIdipp = C[N(CH-2,6- iPr)CH]) with Na[Tp'Mo(CO)(PMe)] (Na-1) in the ratio 1:2 afforded the reddish-brown metallasilylidyne complex [Tp'(CO)Mo≡Si-Mo(CO)(PMe)Tp'] (Tp' = κ- N, N', N″-hydridotris(3,5-dimethylpyrazolyl)borate) (2), in which an almost linearly coordinated silicon atom (∠(Mo1-Si-Mo2) = 162.93(7)°) is bridging the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 125 publications
6
35
0
2
Order By: Relevance
“…Single crystal X‐ray analysis for both compounds revealed that the transition metals adopt a close‐to‐octahedral coordination sphere with five terminal carbonyl ligands (Figures 7 and 8). The Si2−Mo bond length of 2.6629(7) Å is at the upper end of the reported range for Si−Mo bond lengths (2.41–2.71 Å) [21,24] . In close analogy, the Si2−W bond of 2.6594(4) Å is also long in comparison to previously published examples (2.34–2.67 Å) [21,22,25] .…”
Section: Resultssupporting
confidence: 63%
“…Single crystal X‐ray analysis for both compounds revealed that the transition metals adopt a close‐to‐octahedral coordination sphere with five terminal carbonyl ligands (Figures 7 and 8). The Si2−Mo bond length of 2.6629(7) Å is at the upper end of the reported range for Si−Mo bond lengths (2.41–2.71 Å) [21,24] . In close analogy, the Si2−W bond of 2.6594(4) Å is also long in comparison to previously published examples (2.34–2.67 Å) [21,22,25] .…”
Section: Resultssupporting
confidence: 63%
“…In Complexes 35 (Mo) 49 and 36 (Co) 50 have been studied in detail by computational methods. Importantly, both complexes have two •-bonding orbitals (1• and 2•) and two orthogonal πbonding orbitals (1³ and 2³) described in Figure 6, which can explain the formation of the M=Si=M bonding.…”
Section: New Multiple Bonded Systems With Sp-hybridized Ge and Simentioning
confidence: 99%
“…[54][55][56][57][58][59][60] More recently, however, the first bridging silicon centers have also been reported within different transition metal systems. 61,62 We also investigated the electronic structures of germylene 2 and germanium-bridged complex 3 computationally. Natural bond orbital analysis of rhenium-germylene 2 revealed a nearly identical bonding scheme to rhenium-silylene 1a.…”
mentioning
confidence: 99%